Predictors of Quality of Life Improvement after 2 Years of Coronary Artery Bypass Surgery - Peric, Vladan (Ann Thorac Cardiovasc Surg, 2017)
Purpose: The aim was to examine the predictors of improvement of quality of life after 2 years of coronary artery bypass grafting (CABG). Methods: In all, 208 patients who underwent the elective CABG at the Institute for Cardiovascular Diseases Dedinje in Belgrade were contacted and examined 2 years after the surgery. All patients completed Nottingham Health Profile Questionnaire part one. Results: Two years after CABG, quality of life (QOL) in patients was significantly improved in all sections compared to preoperative period. Independent predictors of QOL improvement after 2 years of CABG were found to be serious angina under sections of physical mobility [p = 0.003, odds ratio (OR) = 1.76, 95% confidence interval (CI) 1.21–2.55], energy (p = 0.01, OR = 1.63, 95% CI: 1.11–2.38), sleep (p = 0.005, OR = 1.65, 95% CI: 1.16–2.35), pain (p <0.001, OR = 2.43, 95% CI: 1.57–3.77), absence of hereditary load in energy section (p = 0.002, OR = 0.35, 95% CI: 0.18–0.68), male sex in the sleep section (p = 0.03, OR = 0.43, 95% CI: 0.20–0.93), and absence of diabetes in pain section (p = 0.006, OR = 0.27, 95% CI: 0.10–0.68). Conclusion: Predictors of improvement of QOL after 2 years of CABG are serious angina, absence of hereditary load, male sex, and absence of diabetes.